HUBUNGAN ANTARA PENGUASA DAN RAKYAT DALAM PERSPEKTIF FIQIH SIYASAH - Darwis, Muhammad (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2012)
The ruler and the people are two different strengths. Rulers need people, not only as a legitimate force but also as a force to carry out responsibilities in responsibility. While the people delegate their sovereignty to the ruler with the intention that people gain comfort in managing their lives. The combination of these two forces between the rulers and the people, will be the channel to realize the benefit together. Moreover, any model of governance in a country, the main objective is to establish the laws of Allah. for the realization of the benefit. In fact, these conditions are often inversely so it does not manifest benefit together. Therefore, this issue will be examined from the point of view of jurisprudence siyasah the focus of study rights and obligations of the ruler and the people.